Factors Affecting Microfinance Performance in Nepal - Rana , Bishal (Devkota Journal of Interdisciplinary Studies, 2024)
This study aims to identify the primary determinants of the operational performance of Microfinance Institutions (MFIs) in Nepal, with the objective of determining the key factors that influence their sustainability and effectiveness. The study employs descriptive, correlational, and causal-comparative research methodologies to establish significant relationships between MFI performance and critical variables, such as information technology adoption, loan-lending systems, and regulatory frameworks. The most significant determinant among these is regulatory compliance, which underscores its critical role in enhancing the overall performance and resilience of MFIs in Nepal. The study examines the efficiency of MFIs in the context of the major determinants, as well as factors such as employee motivation, management systems, and risk management practices. It concludes that these factors have a negligible impact. The findings emphasize the transformative role of digitalization, robust regulatory structures, and efficient loan disbursement mechanisms in improving the operational and financial sustainability of MFIs. These insights provide actionable guidance for stakeholders, including policymakers, regulators, investors, and financial institutions, to foster sustainable growth and service delivery in the microfinance sector. The research aligns with recent data from Nepal Rastra Bank (NRB, 2023), underscoring the increasing importance of technological integration and structured lending frameworks in driving MFI success. This study contributes to the broader discourse on financial inclusion and poverty alleviation through targeted microfinance interventions in Nepal